Adsorption of Methylene Blue on Carbon Nanotubes from Aqueous Solutions - Zhao, Donglin; Ding, Yi; Chen, Shaohua; Bai, Tingting; Ma, Yunlei (Asian Journal of Chemistry, 2013)
In this study, the adsorption of methylene blue on carbon nanotubes from aqueous solutions has been investigated in a batch process. Experiments have been carried out to investigate the effects of temperature, methylene blue concentration, pH, carbon nanotubes mass on methylene blue adsorption. The experimental results show that the methylene blue adsorption rate increases with its concentration in the aqueous solutions. Methylene blue adsorption also increases with temperature. The removal of methylene blue from the solution increases as carbon nanotubes mass increases. The kinetic study manifests that the adsorption of methylene blue on the carbon nanotubes is in good compliance with the pseudo-second-order kinetic model.